Old English psalms - O'Neill, Patrick P. (Dumbarton Oaks medieval library, 2016)
"The Psalter, with its 150 psalms, is the longest book of the Bible. For the Anglo-Saxons it was also the preeminent work of the Old Testament. It had several claims on them: as a wisdom book composed in poetry; as the basic classroom text used to teach clerical students how to read and write Latin; and as the central text of the Divine Office. In this last function the psalms were recited at seven mandated times of the day (the Hours) in what was the most important ritual of Christian liturgy after the Mass. But what sets the Anglo-Saxons apart from other western European cultures was their engagement with the psalms in the vernacular. They knew that the Latin Psalter which they inherited from Roman and Irish missionaries had undergone several stages of translation, from its original Hebrew into Greek, and from Greek into Latin. This awareness may well have encouraged them to embark on the hazardous undertaking of translating it yet again from Latin into Old English. That Anglo-Saxon vernacularization of the psalms took three forms: the word-for-word translation (a "gloss"), with the Old English rendering in each case written in smaller script above the corresponding Latin word of the main text. The second mode of translation was prose paraphrase, an advance on the gloss, since the emphasis shifted from focus on the individual word to conveying the meaning of psalm verses in idiomatic sentences. The Old English paraphrase of Psalms 1 to 50, attributed by many to King Alfred (hereafter referred to as the Prose Psalms) exemplifies this development. The third mode of translation, adopted in the Metrical Psalms, maintained the focus on a literal rendering, while recasting the psalms in the medium of Anglo-Saxon poetry."--Provided by publisher